Revolutionizing the road: How sustainable, autonomous, and connected vehicles are changing digital mobility business models - Hugo Pérez-Moure; Jesús F. Lampón; Maria-Elena Velando-Rodriguez; Lorenzo Rodríguez-Comesa\~na (European Research on Management and Business Economics (ERMBE), 2023)
Major trends in the automotive industry are reconfiguring digital mobility business models. From a comprehensive, combined Dynamic Capabilities and Ecosystems approach, this study characterizes the digital mobility business models linked to sustainability, connectivity, and Autonomous Vehicles (AVs) adopted by four carmakers (Volkswagen, Stellantis, Toyota, and Honda). Results show that carmakers differ in their focal digital mobility value propositions, based mainly on the carmakers' own mobility strategies. Volkswagen exhibits an integral proposition with personalized services, while Stellantis is focusing on electric mobility and its solutions, Toyota on autonomous and connectivity services, and Honda on a user-centric perspective via connected and shared mobility. The main sources of income are multiple personalized services linked to connectivity that specifically provide driver assistance, along with remote and digital platform services. Those carmakers pursuing sustainable, autonomous, or shared mobility strategies find their primary income sources in services like remote electric driving, autonomous door-to-door deliveries, and car-sharing. Such services are deployed not only due to technical resources, such as digital skills and data exchange systems, but primarily through organizational capabilities like a "team-player mentality" and a customer-focused vision. Finally, differences in sustainability have been highlighted, but in general terms, all manufacturers are striving to address the battery and charging-point issue through various business models to promote electric mobility. Carmakers are governing a digital mobility ecosystem configured by multiple service and technology providers that are developing transportation solutions.
Keywords: L62; O33; Q55; L91; M15; 650; Sustainability; Mobility; Connectivity; Autonomous vehicles; Digitalization; Business models